Rigidity‐Flexibility Regulation and Hard‐Soft Donor Combination: Dual Strategies in Covalent Organic Frameworks Construction for Actinides/lanthanides Separation - Cao, Run‐Jian; Zhou, Heng‐Yi; Wu, Qun‐Yan; Xiao, Zhe; Xiu, Tao‐Yuan; Li, Jie; Tang, Hong‐Bin; Yuan, Li‐Yong; Wu, Wang‐Suo; Shi, Wei‐Qun (Advanced materials (Weinheim), 2025)
Separating actinides from lanthanides is essential for managing nuclear waste and promoting sustainable nuclear energy development. The recycling of transuranium elements (TRUs: Np, Pu, Am) is also significant for various nuclear technology applications. In this study, a dual strategy is introduced to designing covalent organic frameworks (COFs) that skillfully combines molecular rigidity with flexibility, integrating both hard and soft donor atoms in the synthesis of monomers. This results in a specialized COF that efficiently and selectively captures TRUs from acidic aqueous solutions. By utilizing the topological arrangement of rigid ligands to influence the twisting and stretching of flexible ligands, coordination environment featuring nitrogen and oxygen is created, which enhances the separation of transuranium in various oxidation states over lanthanides. In 0.5 m HNO3 solution, the as‐synthesized DAPhen‐COF achieves removal rates of 99.1% for Np(V) and 95.8% for Pu(IV). For Am(III), the removal rate reaches 98.6% in 0.01 m HNO3. DAPhen‐COF exhibits remarkable selectivity for Np(V), with a separation factor of over 5000 for Np/Gd, outperforming other solid‐phase materials. This research provides a comprehensive investigation into the design and synthesis of COFs for actinide capture, marking the first application of COFs in the separation of various TRUs over lanthanides. A dual strategy for the design of covalent organic frameworks integrates molecular rigidity–flexibility regulation with hard–soft atom incorporation. The synthesized DAPhen‐COF achieves over 95% removal of Np(V), Pu(IV), and Am(III), with a separation factor exceeding 5000 for Np/Gd. This study marks the first application of covalent organic frameworks in separating various transuraniums from lanthanides.